Media wobec fake newsów – motywy kreowania, przyjmowane postawy, podejmowane działania - Daniel, Krystian (Polityka i Społeczeństwo, 2020)
The article is devoted to reflection on the attitudes of professional media (especially the news media) towards false information (fake news). The aim of the analysis was to establish the motives behind the creation and dissemination of such information by the media, as well as actions and attitudes adopted after its publication. The findings were presented based on an analysis of various cases of fake news, mainly from the political sphere. The author points out that similar media deal with fake news in a similar way assuming the same actions and attitudes. The way the media behave also shows an instrumental approach to fake news as a means or a tool to achieve a certain goal.